Electron microscopy, XRD, Mossbauer and dielectric studies of Pb(Fe0.5Nb0.5)1-xSnxO3 multiferroic ceramics. Issue 1 (27th May 2016) - Raevskaya, S. I.; Titov, V. V.; Raevski, I. P.; Kubrin, S. P.; Chen, H.; Chou, C.-C.; Sarychev, D. A.; Shevtsova, S. I.; Malitskaya, M. A.; Zakharchenko, I. N.
ABSTRACT: Multiferroic Pb(Fe0.5 Nb0.5 )1-x Snx O3 (x = 0.025, 0.05, 0.075, 0.10) ceramic compositions were prepared by solid state synthesis and usual sintering. XRD studies have shown a formation of the perovskite structure in all the compositions studied. However, a small amount of pyrochlore phase was detected in Sn-doped compositions with x ≥ 0.05. Scanning electron microscopy studies have shown that at the boundaries of the large grains there exist a lot of small submicron grains enriched by Sn. Concentration dependencies of the unit-cell parameter and ferroelectric phase transition temperatures also imply that solubility of Sn in PFN is limited to ≈ 5 at.%.